Differences in work–family conflict: which individual and national factors explain them?. Issue 3 (4th February 2017) - Ollo-López, Andrea; Goñi-Legaz, Salomé
Abstract: This paper contributes to cross-cultural literature on work–family relationships by testing not only hypotheses about the impact of work and family demands and gender at individual level on work–family conflict (WFC), but also at country level. Concretely, several theories commonly used in the literature (role conflict, boundary management and social support theory) are used to analyzed how national culture dimensions affects WFC. Using information about employee residents in each of the countries interviewed in the Second European Quality of Life Survey and also GLOBE dimensions of national culture, the paper shows that the relationship between work and family demands and WFC is universal and equal phenomenon throughout Europe. In line with gender role theory, demanding and stressing work have stronger effects on women's WFC than on men's. While opposite to it, household hours also have stronger effect on women's WFC than on men's. Moreover, the paper shows that national culture affects how people perceive work–family relationships. In line with integration/segmentation hypotheses derived from boundary management theory, uncertainty avoidance decreases WFC. Moreover, in line with social support, human orientation decreases the level of WFC, especially for men. Eastern Europe and Mediterranean countries have higher levels of WFC, while Scandinavian countries are those that have lower levels of WFC.